Characterization of Vibrio vulni¢cus isolated from cockles (Anadara granosa): antimicrobial resistance, plasmid pro¢les and random ampli¢cation of polymorphic DNA analysis - Son, Radu; Nasreldin, Elhadi; Zaiton, Hassan; Gulam, Rusul; Samuel, Lihan; Nimita, Fifadara; Yuherman, Y; Endang, Purwati (Elsevier Science, Ltd., 1998)
Antibiotic susceptibility, plasmid profiles and random amplification of polymorphic DNA (RAPD) were used to study strains of Vibrio vulnificus isolated from cockles (Anadara granosa). Thirty-six isolates were analyzed. The prevalent biotypes were 1 (72.2% of the isolates) and 2 (27.8%). Among these, 21 strains of biotype 1 and two strains of biotype 2 contained plasmid DNA bands ranging in size from 1.4 to 9.7 MDa. Thirty-one (83.3%) were found to be resistant to one or more of the antimicrobial agents tested, however no specific correlation between antimicrobial resistance patterns and a single biotype was found. In addition, no particular plasmid profile was predictive of a particular pattern of antibiotic susceptibility. Two primers produced polymorphisms in all strains tested, producing bands ranging from 0.25 to 2.7 kb, indicating a high variability among both biotype 1 and biotype 2 of the V. vulnificus strains investigated. RAPD identity across biotypes was also observed among Vibrio vulnificus strains.